Composing the citizen : music as public utility in Third Republic France - Pasler, Jann (Ahmanson Foundation book in the humanities., 2009)
In a work that challenges modernists ideas about the value and role of music in Western society, 'Composing the Citizen' demonstrates how music can help forge a nation.